أثر القصص القرآني في تهذيب النفس الإنسانية - دراسة موضوعية - - لجد صيد, بشيرة (University of Eloued جامعة الوادي‎, 2017)
تناول هذا البحث الموسوم بعنوان " أثر القصص القرآني في تهذيب النفس الإنسانية- دراسة موضوعية –" دراسة القصة القرآنية وبيان أثرها في تهذيب النفس الإنسانية ، وذلك من خلال انتقاء نماذج من القصص القرآني وتقسيمها بحسب موضوع النزعة التي تعالجها ، ثم بيان آيات القصة وتفسيرها ، وفي بعض الأحيان تقسيمها إلى عناصر يتبين من خلالها موضوع القصة ، ثم استنباط دروس وعبر تربوية من كل نموذج قصصي حيث يلمح من خلال هذه الدروس الأثر التهذيبي للقصة القرآنية . حاول هذا البحث بيان الأثر أو الدور الذي تلعبه القصة القرآنية في تهذيب نوازع النفس بمختلف مجالاتها سواءً على مستوى العقل أو الوجدان والشعور أو الشهوات . ولقد توصل هذا البحث إلى نتائج أهمها: أن للقصة القرآنية أثرا قويا في تهذيب النفس وتعديل سلوكياتها وكان ذلك من خلال عدة وسائل منها: ضرب نماذج إيجابية وسلبية الأولى للقدوة والثانية للعبرة و استثارة الوجدان والمحاكمة العقلية و تعريف الإنسان بذاته والترغيب والترهيب والحضور الإلهي وغرس عقيدة البعث والجزاء، ولكل هذه الوسائل أثرٌ فعال في تربية النفس وتعديل سلوكياتها . This study deals with the study of the Qur'anic story and its impact on the human soul by selecting examples of Quranic stories and dividing them according to the subject of the tendency to be dealt with, and then explaining the verses of the story and interpreting them, and sometimes dividing them into elements through which the story is revealed. Educational aspect of each narrative model, through which these lessons hint at the deceptive effect of the Qur'anic story. This research attempts to explain the impact or role played by the Qur'anic story in the refinement of the self-interest in all its domains, whether on the level of reason, conscience, feeling or desires. This research has reached the most important results: The Quranic story has a strong impact on the refinement of the soul and the modification of its behavior. This was done through several methods, including: striking positive and negative examples of the first example and the second of the phrase, arousing the conscience, the mental trial and the definition of the individual, , Instilling the doctrine of Baath and punishment, and each of these means an effective impact in raising self and adjusting its behavior.
مذكرة ماستر تخصص علوم القرآن
Keywords: القصص القرآني-النفس; Quranic stories - self